Exploring the experiences of residents and their families in an alcohol-related brain injury residential rehabilitation unit in Northern Ireland: a qualitative study - Campbell, Anne; Millen, Sharon; Jordan, Uisce; Watson, Diane; Watson, Joy; McCorry, Roger (Frontiers in Public Health, 2024)
Objective Limited research exists on comprehensive interventions for individuals with Alcohol Related Brain Injury (ARBI). Exploring the impact of a rehabilitation service on individuals with ARBI and their relatives/caregivers, this study aimed to gain insights into their experiences and assess how the service influenced cognitive functioning, psychological well-being, social relationships, community engagement, and the desire for abstinence. Method This was a qualitative, semi structured interview study as part of a larger mixed methods study of residents and their family members. Data was collected over 4 timepoints with n = 20 residents: baseline (n = 20 interviews), 6 months (n = 15 interviews), 12 months (n = 6 interviews) and at discharge (n = 8 interviews). The interviews took place at a specialist residential rehabilitation facility for people with ARBI. Remote interviews were conducted with family members (n = 10). A thematic analysis of transcripts using NVivo software was undertaken. Results Qualitative findings for residents with ARBI across 4 timepoints from baseline to time of discharge indicated an improvement in all outcomes. Overall, residents reported that the ARBI holistic intervention improved psychological wellbeing, social relationships/community participation, functioning abilities, and abstinence from alcohol, particularly when residents were residing in the unit. Family members and carers presented more trepidation regarding the long-term impacts. Conclusion Whilst the residential unit provided structure and a protective environment, residents required ongoing support post discharge for their addictive behaviours. An outreach intervention for these individuals is currently being piloted.